In plain sight – developing strategic responses to corporatised organised crime. Issue 2 (16th January 2020) - Murray, Kenneth
Abstract : Purpose: This paper aims to consider the ways organised crime exerts influence in legitimate commercial markets through its ability to act through corporate vehicles. Discussion of weaknesses in company registration procedures and the criminal justice system that enable this to happen. Development of strategic rather than tactical responses is proposed to counter it. Design/methodology/approach: The paper presents case studies based on practitioner experience and discusses points that arise. Findings: This paper considers the extent to which the problem represents a threat to the well-being and competitiveness of domestic commercial markets and how these threats can be most effectively addressed. Research limitations/implications: This is a point of view paper authored by a practitioner with professional expertise in the field. Practical implications: There is a need to develop strategic cross-agency responses to this problem. This will develop better levels of precautionary awareness of how these influences can establish footholds in commercial markets and provide a sounder basis for taking effective measures to contain and counter their influence. Social implications: The social implications relate to the distorting influence of money derived from crime being deployed in legitimate spheres. Originality/value: The originality/value of this paper is to raise awareness and re-invigorate discussion on the influence of organised crime in legitimate commercial markets.